Finite element analysis of fatigue damage of composite laminated structures - Hegaze, Moutaz Mohamed Ebrahim (Cranfield University, 2002)
Composite materials are increasingly believed to be the materials of the future with potential for application in high perfon-nance structures. One of the reasons for that is the indication that composite materials have a rather good rating with regard to life time in fatigue. Fatigue of composite materials is a quite complex phenomenon, and the fatigue behaviour of these heterogeneous materials is fundamentally different from the behaviour of metals. Finite element method is a powerful numerical technique for the solution of such complex problems. The present work comprises theoretical and experimental research into the implementation of composite materials in structure applications. A new finite element derivation was carried out based on a high-order shear deformation theory, which is accurate for a wide range of thickness. The geometric nonlinearity effect was considered in the derivation of the element. The force increment method was also introduced to improve the accuracy of nonlinear analysis. Experimental measurements were carried out with two different types of composite materials, carbon/epoxy and glass/epoxy, in order to obtain fatigue life diagrams (S/N diagrams) to be used for the fatigue damage assessment.F atigue damage assessmentsw ere developed to predict the fatigue behaviour of laminated plates and shells based on two aspects; damage by initiation and damage by crack growth. A computer package was built based on the proposed finite element theory to carry out the previous analyses. Several finite element solvers and eigenproblem solvers are available to users of the package to choose the suitable one for their applications. The validation of the developed package for some analyses such as stress analysis, natural frequency analysis, stability analysis and fatigue analysis was successfully achieved using a number of composite case studies. A parametric study was also carried out to illustrate the potential of the package to be used as a good optimization tool. Fatigue life assessment by damage growth has been achieved by a single run of the package, thus saving enormous user effort and computer resources, compared with the use of commercial finite element packages.